(untitled) (International Association of Biologicals and Computational Digest, 2023)
The production and implementation of synthetic dyes generate significant waste and unfixed colorant. Which raises health risks, and pollution and disrupts eco-balance. Nature has always dominated over synthetic or artificial materials since the beginning of time because nature was the only choice for humans at the time, and now with the advantageous properties of naturally derived materials over synthetics, they have priority(Yusuf et. al., 2017). Safflower is an all-natural red dye that is frequently used to color cotton. It includes the well-known constituents reddish carthamin and yellowish safflower yellow. In the present study, the dyeing behaviour of safflower is examined by the use of an aqueous method and different mordants on linen, cotton, and silk. The relationship between the dye-uptake of linen, cotton, and silk fabric investigated with the various dyeing conditions is discussed.